Concept and behaviour of pressure politics in India - Srivastava, B. K. (Bhopal, 1983)
Pressure Politics has assumed signi ficant role in the Decision-making. Various groups as a by-product of political culture crop up in the bound ary of society and polity. If the channels of political communication were not open to masses, these groups dominate in the infrastructure. During the decade of 1970s, particularly after the first spilt of the Congress in 1969 pressure groups assumed a new dimension in the political process of India which ultimately culminated in the imposition of emer gency. Diverse pressure groups aggre gated their interest in the Congress fold and operated in and out of the formal decision making institutions without any official recognition or acknowledg ment. The author has revealed the role performance of these groups in a very scientific manner. His analysis is based on the conceptual design of behavioural approach. It is the first book of its kind on the subject.
Keywords: Pressure Groups - India